Project-based Learning in Translation Courses: An Implementation and Students’ Perception - Lafziatul Hilmi; Dian Safitri (Journal of English Language Teaching, 2022)
Translation is one of the useful and beneficial competencies for English students; it is not only to achieve the learning outcomes during their study but also to be a valuable skill that they can use to get a job after graduation. This study aims to introduce project-based learning and its implementation and to explore students' perceptions in deploying project-based learning as the learning method in translation courses. This study was a qualitative study with a case study method design. The data of students' perceptions were attained through an online questionnaire containing close-ended and open-ended questions. The participants were 38 students who took the Basic Translation and Interpretation course. The data were analyzed narratively to describe the implementation of project-based learning and students' perception of its implementation in translation courses. The study showed that students' perception toward PjBL projects was positive and actively engaging students in completing activities of the projects.